Pelatihan Penggunaan Aplikasi Faststone Capture dalam Menyusun Bahan Ajar untuk Pembelajaran Matematika Model Flipped Classroom - Riki Andriatna; Imam Sujadi; Budiyono; Ira Kurniawati; Arum Nur Wulandari; Hanifa Alifia Puteri (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2022)
This activity was motivated by the problem of not optimal online learning in the Covid-19 pandemic situation. In particular, there are still teachers who do not know how to learn with the flipped classroom model, especially in the preparation of flexible teaching materials. Problems with mathematics teacher partners in Surakarta city can be solved, one of which is training in the use of technology applications, namely the Faststone Capture application which functions to capture screens, record, and edit to the screenshots to produce better teaching materials. The stages of activities carried out to solve problems are as follows: (1) socialization of mathematics learning with the flipped classroom model assisted by IT-based media with the aim of making mathematics learning plans; (2) introduction and use of faststone capture applications with the aim of developing mathematics teaching materials by utilizing faststone capture; and (3) dissemination of training results. The training activities provide knowledge to mathematics teachers regarding the use of faststone capture applications in compiling teaching materials that support mathematics learning through the flipped classroom model.